2006
DOI: 10.3390/medicina43030029
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient methadone maintenance treatment program Quality of life and health of opioid-dependent persons in Lithuania

Abstract: Background. The evaluation of quality of life and self-perceived health represents an assessment of the impact of treatment on patient functioning and well-being. Objective. Our aim was to explore the impact of methadone maintenance treatment on quality of life and self-perceived health of opioid-dependent persons in Lithuania. Methods. A total of 102 opioid-dependent patients were recruited in the study. A prospective follow-up study design was used. To assess quality of life, the WHOQOL-BREF 26-item version … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
2
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 33 publications
5
42
2
5
Order By: Relevance
“…In this study quality of life scores were shown to have improved in direct proportion to the MMT duration; nevertheless. Only the social subscale score was reported to be statistically significant, this was contrary to others findings, 16,29,30 which can probably best explained by the fallacy on the part of addicts' family hoping for MMT to be a magic bullet. Other plausible reason why MMT may fail at times possibly regards unemployment as a result of social alienation, discrimination and stigma against drug users.…”
Section: Discussioncontrasting
confidence: 55%
“…In this study quality of life scores were shown to have improved in direct proportion to the MMT duration; nevertheless. Only the social subscale score was reported to be statistically significant, this was contrary to others findings, 16,29,30 which can probably best explained by the fallacy on the part of addicts' family hoping for MMT to be a magic bullet. Other plausible reason why MMT may fail at times possibly regards unemployment as a result of social alienation, discrimination and stigma against drug users.…”
Section: Discussioncontrasting
confidence: 55%
“…QoL is an overarching concept, which has often been applied in health care research (Padaiga et al 2007), particularly in the fields of disability studies and mental health care (Masthoff et al 2005;Schalock 2005). Nevertheless, there is controversy over the meaning of this concept, and there is no consensus about its definition (Carr and Higginson 2001;Fischer et al 2001a, b;Moons et al 2006;Taillefer et al 2003).…”
Section: The Concept Of Qolmentioning
confidence: 99%
“…Isolation and social stigma may contribute to the fact that social inclusion is often difficult to achieve. Padaiga et al (2007) have demonstrated that stigmatization may have an influence on understandings of QoL. In the field of mental health care, stigma appears to have negative consequences for the QoL of clients and frequently results in discrimination (Rosenfield 1997).…”
Section: More Than Health-related Quality Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…El éxito del tratamiento depende de otros factores, tales como el empleo, las relaciones familiares, la disponibilidad de relaciones íntimas, la estructuración horaria de las actividades de la vida diaria y el cambio de hábitos relacionados con la salud, entre otros (De Maeyer, Vanderplasschen, Lammertyn et al, 2011;He et al, 2011). Estos programas parten de la consideración de que la respuesta al tratamiento es función de diferencias individuales y no una mera función farmacológica dosis-respuesta (Padaiga, Subata y Vanagas, 2007). Desde esta perspectiva, no cabe hablar de dosis altas o bajas, sino dosis ajustadas o adecuadas, que eliminen la necesidad (pero no la posibilidad) de que se produzcan consumos adicionales.…”
unclassified